Probing the interaction between 2D materials and oligoglycine tectomers. (1st October 2022) - Tripathi, Manoj; Garriga, Rosa; Lee, Frank; Ogilvie, Sean P; Graf, Aline Amorim; Large, Matthew J; Lynch, Peter J; Papagelis, Konstantinos; Parthenios, John; Cebolla, Vicente L; Jurewicz, Izabela; Dalton, Alan B; et al.
Abstract: Heterostructures of two-dimensional (2D) materials using graphene and MoS2 have enabled both pivotal fundamental studies and unprecedented sensing properties. These heterosystems are intriguing when graphene and MoS2 are interfaced with 2D sheets that emulate biomolecules, such as amino-terminated oligoglycine self-assemblies (known as tectomers). The adsorption of tectomer sheets over graphene and MoS2 modulates the physicochemical properties through electronic charge migration and mechanical stress transfer. Here, we present a systematic study by Raman spectroscopy and tectomer-functionalised scanning probe microscopy to understand mechanical strain, charge transfer and binding affinity in tectomer/graphene and tectomer/MoS2 hybrid structures. Raman mapping reveals distinctive thickness dependence of tectomer-induced charge transfer to MoS2, showing p-doping on monolayer MoS2 and n-doping on multilayer MoS2 . By contrast, graphene is n-doped by tectomer independently of layer number, as confirmed by x-ray photoelectron spectroscopy. The interfacial adhesion between the amino groups and 2D materials are further explored using tectomer-functionalised probe microscopy. It is demonstrated here that these probes have potential for chemically sensitive imaging of 2D materials, which will be useful for mapping chemically distinct domains of surfaces and the number of layers. The facile tectomer-coating approach described here is an attractive soft-chemistry strategy for high-density amine-functionalisation of atomic force microscopy probes, therefore opening promising avenues for sensor applications.